2021
DOI: 10.1108/itp-09-2020-0632
|View full text |Cite
|
Sign up to set email alerts
|

AI-powered learning application use and gratification: an integrative model

Abstract: PurposeAs the center of the fourth industrial revolution, artificial intelligence (AI) has marked its presence in various disciplines including the education field in the form of AI-powered learning applications. The purpose of this study is to build a research model capturing the relationships among use contexts, user gratification, attitude, learning performance and continuous intention to use an AI-powered English learning application.Design/methodology/approachUsing the use and gratification theory, use co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Specifically, participants believed that their reading aloud skills, fluency, and pronunciation improved the most. The findings are in accordance with other research examining the perceived effectiveness of AI speaking apps in enhancing speaking skills (Chang et al, 2022;Rosell-Aguilar, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, participants believed that their reading aloud skills, fluency, and pronunciation improved the most. The findings are in accordance with other research examining the perceived effectiveness of AI speaking apps in enhancing speaking skills (Chang et al, 2022;Rosell-Aguilar, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Some AI speech evaluation programs can provide automatic feedback including scores and text-based feedback, such as Duolingo (Rachels & Rockinson-Szapkiw, 2018), Babbel (Loewen et al, 2020), Rosetta Stone (Nielson, 2011), Liulishuo (Chang et al, 2022), and so on. These programs were claimed to be effective in improving EFL learners’ speaking skills (e.g., Chang et al, 2022; Loewen et al, 2019, 2020; Rosell-Aguilar, 2018). For instance, Loewen et al (2019) analyzed the effectiveness of Duolingo by recruiting one group of participants ( n = 9) to study Turkish as their second language for a semester.…”
Section: Introductionmentioning
confidence: 99%
“…is the most successful of the gamification platforms. Researchers have found that the features and functionalities of media platforms are important in determining people's choices in using the media (Chang et al, 2022;Hong et al, 2020). The perceptions of people in relation to the features are thus the decisive factor.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…"Artificial intelligence refers to the intelligence performed on a task by the digital computer or the robot" (Nilsson, 1998, p. 1). AI allows computer systems to learn automatically from experience and complete human-like tasks to improve productivity (Złotowski et al, 2014;Chang et al, 2021). Wirtz et al (2018) defined service robots as "system-based autonomous and adaptable interfaces that interact, communicate, and deliver service to an organization's customers" (p. 909).…”
Section: Literature Review 21 Ai Service Robots In the Service Industrymentioning
confidence: 99%
“…AI allows computer systems to learn automatically from experience and complete human-like tasks to improve productivity (Złotowski et al. , 2014; Chang et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%